2018
DOI: 10.31871/wjir.5.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Trends of Rainfall and Temperature in the Amboseli Ecosystem of Kenya

Abstract: This study investigated spatial and temporal trends of rainfall and temperature in the Amboseli ecosystem of Kenya. The analysis were based on historical Climate Hazards group InfraRed Precipitation with Station (CHIRPs) and Climate Hazards group InfraRed Temperature with Station (CHIRTs) data for the period 1960-2014 and the period 2006-2100 for the projections. This data was used due to limitations in the observed station data. Projections of rainfall and temperature were based on Regional Climate Models (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
(47 reference statements)
2
3
0
1
Order By: Relevance
“…The decreasing trend in rainfall in the study area could result to frequent occurrence of drought incidences causing a significant reduction in crop yields as well as pasture and water shortage for livestock production which are key sources of livelihood in the region. The findings are in consonance with results from a similar study by Aduma et al (2018) which indicated a non-significant declining trend in annual rainfall in the Amboseli Ecosystem of Kenya. A similar trend in annual rainfall was also recorded along the Coastal Tanzania by Mahongo and Francis (2012).…”
Section: Rainfall Trends and Variability In The Study Areasupporting
confidence: 90%
See 1 more Smart Citation
“…The decreasing trend in rainfall in the study area could result to frequent occurrence of drought incidences causing a significant reduction in crop yields as well as pasture and water shortage for livestock production which are key sources of livelihood in the region. The findings are in consonance with results from a similar study by Aduma et al (2018) which indicated a non-significant declining trend in annual rainfall in the Amboseli Ecosystem of Kenya. A similar trend in annual rainfall was also recorded along the Coastal Tanzania by Mahongo and Francis (2012).…”
Section: Rainfall Trends and Variability In The Study Areasupporting
confidence: 90%
“…Similarly, Le and Pricope (2017) reported that CHIRPS dataset had a greater temporal correlation with the in situ station data in Nzoia Basin, Western Kenya. CHIRPS datasets have been used to analyze precipitation trends in similar studies in East Africa (Aduma et al, 2018;Cattani et al, 2021;Gebrechorkos et al, 2019;Kerandi et al, 2017).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Mo s t o f t h e f a r m e r s' perceptions of temperature trends indicated that there was an increase in the number of hot days [16,17]. Similar results showing substantial increase in both Tmin and Tmax in Kenya were also reported by some other researchers [29,33,57,58].…”
Section: Comparing Farmers' Perception With Meteorological Datasupporting
confidence: 80%
“…With increasing trends in annual temperature, there is the need to understand how such trends will affect agricultural systems in the ASALs and how farmers will need to adjust to CC risks such as moisture and heat stress. [58], which established that there was a higher increase in absolute Tmin compared to Tmax in the Amboseli ecosystem during 1960-2014.…”
Section: Variability and Trends In Annual Maximum And Minimum Temperaturementioning
confidence: 91%
“…Trong một công trình khác, dữ liệu nhiệt độ và lượng bốc hơi nhiều năm cho hệ sinh thái Amboseli ở Kenya được Aduma và cộng sự đánh giá bằng thống kê Mann -Kendall và phân tích xu hướng tuyến tính. Kết quả cho thấy sự gia tăng nhiệt độ và thay đổi lượng mưa có thể tác động lớn đến các nguồn tài nguyên ở các vùng đất khô cằn ở Đông Phi [6]. Đi sâu vào nghiên cứu bản chất và nguyên nhân trong khác biệt khí hậu theo thời gian cho một khu vực, Oscar và cộng sự dựa trên kết quả phân tích tương quan đã đi đến kết luận rằng xu hướng trong một số biến số khí hậu ở vùng Tây Bắc Mexico có liên quan đến sự biến đổi nhiều thập kỷ của hai đại dương lớn cũng như mô hình dòng khí quyển [7].…”
Section: Mở đầUunclassified